Survival outcome and prognostic factors after pancreatoduodenectomy for distal bile duct carcinoma: a retrospective multicenter study - Petrova, Ekaterina; Rückert, Felix; Zach, Sebastian (Langenbeck's archives of surgery, 2017)
Purpose: Pancreatoduodenectomy is the most common operative procedure performed for distal bile duct carcinoma. Data on outcome after surgery for this rare malignancy is scarce, especially from western countries. The purpose of this study is to explore the prognostic factors and outcome after pancreatoduodenectomy for distal bile duct carcinoma. Methods: Patients receiving pancreatoduodenectomy for distal bile duct carcinoma were identified from institutional databases of five German and one Russian academic centers for pancreatic surgery. Univariable and multivariable general linear model, Kaplan-Meier method, and Cox regression were used to identify prognostic factors for postoperative mortality and overall survival. Results: N = 228 patients operated from 1994 to 2015 were included. Reoperation (OR 5.38, 95%CI 1.51-19.22, p = 0.010), grade B/C postpancreatectomy hemorrhage (OR 3.73, 95%CI 1.13-12.35, p = 0.031), grade B/C postoperative pancreatic fistula (OR 4.29, 95%CI 1.25-14.72, p = 0.038), and advanced age (OR 4.00, 95%CI 1.12-14.03, p = 0.033) were independent risk factors for in-hospital mortality in multivariable analysis. Median survival was 29 months, 5-year survival 27%. Positive resection margin (HR 2.07, 95%CI 1.29-3.33, p = 0.003), high tumor grade (HR 1.71, 95%CI 1.13-2.58, p = 0.010), lymph node (HR 1.68, 95%CI 1.13-2.51, p = 0.011), and distant metastases (HR 2.70, 95%CI 1.21-5.58, p = 0.014), as well as severe non-fatal postoperative complications (HR 1.64, 95%CI 1.04-2.58, p = 0.033) were independent negative prognostic factors for survival in multivariable analysis. Conclusion: Distant metastases and positive resection margin are the strongest negative prognostic factors for survival after pancreatoduodenectomy for distal bile duct carcinoma; thus, surgery with curative intent is only warranted in patients with local disease, where R0 resection is feasible.
Gesehen am 12.07.2018